Relação dos acidentes do trabalho com o agronegócio em Mato Grosso e no Brasil, 2008 a 2017 - Fava, Nara Regina (2020)
Accidents at work are related to the production process and are part of studies in the area of Workers' Health. In the 1960s, with the process of expansion of agricultural production driven by the Green Revolution, the economic activities of developing countries have adopted a model called agribusiness. This productive model begins with deforestation, forest exploitation, soil preparation for agriculture and cattle-raising in the plantation, treatment, harvesting, transportation, storage and agro-industry, and at all stages occupational accidents are prevented. The objective was to evaluate the indicators of occupational accidents and relate them to the agricultural and economic production of agribusiness in the Federal States of Brazil and in the municipalities of Mato Grosso from 2008 to 2017. This is an ecological study based on secondary data on the production of the Mato Grosso agribusiness chain, economic indicators and health in Brazil (MT) and the municipalities of Mato Grosso. The population of the study was composed of formal workers from the Brazilian Federation Units and the municipalities of Mato Grosso. For data analysis, incidence, mortality and lethality rates were calculated; for the trend, simple linear regression models were adjusted and annual percentage variation (VPA) and correlation tests were calculated considering the 5% significance level. Thematic maps of health and production indicators were performed. In the first article, it was observed among the UF, Mato Grosso presented the highest death rate with 19.5 deaths/100 thousand formal workers and the second highest lethality rate with 8.7 death/ thousand accidents. When compared with the rates in Brazil, the mortality rate was three times higher, while the lethality rate was twice the national average, of the total of occupational accidents, between 2008 and 2017. The reduction in the incidence rate per occupational accident (AT) was identified from 23.6/thousand workers in 2008 to 14.3, in 2017, and the mortality was from 8.8 deaths/100 thousand workers to 5.5 in the period. The highest incidence rate of AT related to agribusiness was in Alagoas with 37.9, followed by Mato Grosso with 30.4 and Rondônia with 30.3; the highest mortality rate was in Amapá with 41.6/100 thousand workers, followed by Rondônia with 32.8 and Mato Grosso with 31.8; the highest mortality rate was in Tocantins with 18.4 deaths per thousand AT, followed by Roraima with 16.2 and Amapá with 15.5. Agribusiness stood out with the highest decreasing annual percentage (VPA) of TA (-5.5%), as opposed to VPA for the national GDP with an increase of 13.4%. It was found positive and significant correlation between the incidence rates of agribusiness (r=0.509; p=0.007) and industry (r=0.412; p=0.033), with the gross value added (GVA) of agriculture, and positive correlation between the incidence rates of trade (r=0.480; p=0.011) with national GDP. The second article identified a tendency for an increase in the VPA of the productive effort (hectare/inhabitant) of 7.34%, productive effort (agrotoxic/inhabitant exposure) of 6.23%, hospitalizations for neoplasms of 6.24% and mortality for neoplasms of 3.06%, this increase also followed the GVA of farming which was 19.8%. It was identified that in the eco-nomic activities of agribusiness the highest percentages of TA are concentrated, being the first in frigorific (16.9%), the second in agriculture (12.3%) and the sixth in cattle raising (3.5%), showing positive correlations between incidence rates, mortality and mortality of TA (=0.306); p=0.001, r=0.366; p=0.001, r=0.388, p=0.001), respectively, with the gross added value (GVA) of agriculture and the increasing tendency of agricultural production, agricultural inputs and health problems. Among the highest rates of incidents, mortalities and mortality by TA are the largest agricultural producers (Paranatinga, Barra do Garças, Alta Floresta, Sorriso, Brasnorte, Querência, Barão de Melgaço, Confresa and Castanheira) in Mato Grosso and that 58.4% of TA are related to agribusiness. It is concluded that occupational accidents occur in all sectors of the economy in general related to activities developed in the agroforestry and livestock sectors of agribusiness, mineral extraction, construction, industry, transport and trade, since the highest rates are found in UF where one of these economic activities predominate. The reduction of the trend in TA rates may be considered due to the effects of globalization, modernization in work processes, informality and underemployment, which contribute to the increase of underreporting in Brazil. In this way, these results can subsidize the elaboration of strategies that strengthen the Workers' Health Surveillance throughout the national territory aiming at the promotion and prevention of TA in the sectors of higher accidentality.